Humidity‐Responsive Liquid Crystalline Network Actuator Showing Synergistic Fluorescence Color Change Enabled by Aggregation Induced Emission Luminogen. (19th February 2021) - Lan, Ruochen; Gao, Yanzi; Shen, Chen; Huang, Rui; Bao, Jinying; Zhang, Zhongping; Wang, Qian; Zhang, Lanying; Yang, Huai
Abstract: Imitating the structures and behaviors of natural creatures is of great significance to scientists to explore novel materials for practical applications. However, the design and fabrication of biomimetic devices with complex and outstanding performances is still on the way. A bilayer film composed of liquid crystalline networks (LCN) film and hydrochromic aggregation‐induced‐emission molecule‐doped hydrophilic layer is prepared. Under different relative humidity, the composite film can deform and change fluorescence color simultaneously. The influence of the content of the hydrophilic matrix on the fluorescent property and humidity‐responsive behaviors of the bilayer film is investigated. Thanks to the mechanical anisotropy provided by uniform‐aligned LCN film, different modes of deformation of the bilayer film are achievable, like bending, curling, and twisting. More importantly, due to the independence of the LCN film and the non‐mesogenic molecules brought by this bimorph strategy, complex alignment of the LCN film and modification by immiscible molecules are realized in a single LCN actuator. Based on the functional composite film, artificial flowers showing synergistic blooming and shape‐changing is prepared. By regulating the molecular alignment of the LC mesogens of the LCN film, the artificial flowers can imitate various blooming behaviors of natural flowers like confederate jasmine and jade lotus. Abstract : Humidity‐responsive actuators showing a synergistic shape and fluorescence color change are prepared by integrating a hydrophilic layer and liquid crystalline network in which a vivid fluorescence color change originates from synthesized aggregation‐induced‐emission luminogens. The programmable soft actuator with high tunability in deformation mode and fluorescence properties could provide inspiration for fabricating advanced biomimetic devices.